Properties of the Likelihood Ratio for Counting Processes in the Problem of Estimation of Unknown Parameters - Lin'kov, Yu. N.; Nikolaeva, O. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain an asymptotic decomposition of the logarithm of the likelihood ratio for counting processes in the case of similar hypotheses. We establish the properties of the normalized likelihood ratio in the problem of estimation of an unknown parameter.